2007
DOI: 10.1161/circulationaha.106.658237
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete Stent Apposition and Very Late Stent Thrombosis After Drug-Eluting Stent Implantation

Abstract: Background— Stent thrombosis may occur late after drug-eluting stent (DES) implantation, and its cause remains unknown. The present study investigated differences of the stented segment between patients with and without very late stent thrombosis with the use of intravascular ultrasound. Methods and Results— Since January 2004, patients presenting with very late stent thrombosis (>1 year) after DES implantatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
447
7
31

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 772 publications
(502 citation statements)
references
References 27 publications
17
447
7
31
Order By: Relevance
“…From these results, we reconfirmed that VLST may be rare, but its consequences are dangerous. Procedural and pathologic risk factors such as local hypersensitivity reaction of the stent; ostial and/or bifurcation stenting; malapposition/incomplete apposition of struts 6 ; restenosis; and strut penetration into a necrotic core could affect occurrences of VLST and poor endothelialization has been proposed as the most important pathologic predictor of late stent thrombosis. The latter factors might affect long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From these results, we reconfirmed that VLST may be rare, but its consequences are dangerous. Procedural and pathologic risk factors such as local hypersensitivity reaction of the stent; ostial and/or bifurcation stenting; malapposition/incomplete apposition of struts 6 ; restenosis; and strut penetration into a necrotic core could affect occurrences of VLST and poor endothelialization has been proposed as the most important pathologic predictor of late stent thrombosis. The latter factors might affect long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Statistical Analysis Data are expressed as mean ± standard deviation (SD) for continuous variables and as frequencies for categorical variables. Major adverse cardiac event-free survival distributions were estimated according to the Kaplan-Meier method.…”
Section: Study Outcomes and Definitionsmentioning
confidence: 99%
“…Delayed ischemic events occurred in 8 (16%) of 50 cases, and all cases involved patients with incomplete stent apposition. In patients undergoing drug-eluting stent placement for coronary artery disease, several studies 14,15) suggested that delayed arterial healing and stent malapposition may be important causes of very late stent thrombosis (thrombosis at >1 year after stent deployment).…”
Section: Discussionmentioning
confidence: 99%
“…A previous IVUS study demonstrated that stent malapposition was highly prevalent in patients with very late stent thrombosis after DES implantation. 31 Subsequently, an angiographic registry showed that late acquired peri-stent contrast staining after DES implantation, which might represent an abnormal vessel wall response such as stent malapposition and positive vessel remodeling, was associated with subsequent target-lesion revascularization and very late stent thrombosis 32 (Figure 4). 15.1±4.6 mm 2 , P=0.003) were associated with late stent thrombosis.…”
Section: Acquired Stent Appositionmentioning
confidence: 99%